Moderation Of Moral Identity In Ethical Judgement And Moral Intention Accounting Students - Riski Aprillia NITA; Putri WULANDITYA; Nurul Hasanah Uswati DEWI (PT Keberlanjutan Strategis Indonesia, 2023)
This study aims to determine the factors influencing ethical considerations and moral intentions (such as gender, perceived moral intensity, and perceived moral culture) with moral identity as a moderator. This study uses a survey method for data collection. The research respondents were 169 Hayam Wuruk Perbanas University accounting students who had taken audit courses—data analysis technique using SEM-PLS. The study results show that (1) ethical judgment is only influenced by perceived moral culture. In contrast, moral intention can be influenced by gender, perceived moral intensity, perceived moral culture with moral intention, and moral identity. (2) Moral identity can be a moderator of the effect of perceived moral intensity on moral intention and the influence of perceived moral culture on ethical judgment. This finding has implications for universities to provide a learning process about ethical dilemma cases not only in ethics courses but also in competency courses such as auditing practice.